2021
DOI: 10.3390/s21165617
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Deep Learning EEG Models for Cross-Participant and Cross-Task Detection of the Vigilance Decrement in Sustained Attention Tasks

Abstract: Tasks which require sustained attention over a lengthy period of time have been a focal point of cognitive fatigue research for decades, with these tasks including air traffic control, watchkeeping, baggage inspection, and many others. Recent research into physiological markers of mental fatigue indicate that markers exist which extend across all individuals and all types of vigilance tasks. This suggests that it would be possible to build an EEG model which detects these markers and the subsequent vigilance d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…From the perspective of feature classification, although the differences between tasks corresponding to different EEG signals limit the cross-task versatility of existing classification models (Zhou et al, 2022 ), researchers are still committed to finding or constructing some relatively general cross-task feature classification models (Kamrud et al, 2021 ; Mota et al, 2021 ; Taori et al, 2022 ).…”
Section: Cross-task Eeg Signal Analysis Based On Feature Classificationmentioning
confidence: 99%
See 3 more Smart Citations
“…From the perspective of feature classification, although the differences between tasks corresponding to different EEG signals limit the cross-task versatility of existing classification models (Zhou et al, 2022 ), researchers are still committed to finding or constructing some relatively general cross-task feature classification models (Kamrud et al, 2021 ; Mota et al, 2021 ; Taori et al, 2022 ).…”
Section: Cross-task Eeg Signal Analysis Based On Feature Classificationmentioning
confidence: 99%
“…(1) Neural network method. Kamrud et al studied the commonality of three different models in terms of cross-task: MLPNN, temporal convolutional network (TCN), TCN auto encoder (TCN-AE) (Kamrud et al, 2021 ), and the results showed that the best model for cross-task classification was the MLPNN frequency domain model.…”
Section: Cross-task Eeg Signal Analysis Based On Feature Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…A physiological decrease in vigilance over time is associated with performance degradation, such as slower reaction times and loss of situation awareness, whereas optimal performance is ensured by an adequate level of activation throughout the task (Parasuraman et al, 1998 ). EEG measures have been used as features for machine learning models to monitor vigilance levels in different contexts (Sebastiani et al, 2020 ; Kamrud et al, 2021 ; Li and Chung, 2022 ).…”
Section: Introductionmentioning
confidence: 99%